Nonlinear dynamics of gravitational instability in complex viscoelastic astrofluids - Dhrubajit Kalita; Pralay Kumar Karmakar (AIP Advances, 2018)
The nonlinear evolutionary dynamics of gravitational instability in a complex self-gravitating viscoelastic nonthermal polytropic astrofluid is semi-analytically investigated on the Jeansian scales of space and time. The key effects out of fluid buoyancy, thermal fluctuations, and volumetric expansions are concurrently considered and carefully included. A nonlinear normal mode (local) analysis yields a Korteweg-de Vries (KdV) equation with a unique set of multi-parametric coefficients. We provide a numerical platform to demonstrate how the KdV dynamics excites an interesting spectral class of compressive solitary chain patterns as the evolutionary eigenmodes having atypical dynamical behaviour. Their diversified characteristic features are explained elaborately alongside phase-plane analysis. Various stabilizing (destabilizing) and accelerating (decelerating) factors of the instability are illustratively explored together with a validated reliability checkup. The relevancy of our investigated results in the context of super-dense compact astro-objects and their circumvent viscoelastic atmospheres is summarily outlined.